How Do Unemployed Workers Behave Prior to Retirement? A Multi-State Multiple-Spell Approach - Ewa Gałecka-Burdziak; Marek Góra (Institute of Labor Economics (IZA), 2017)
We examine the behaviour of unemployed older workers up to five years prior to the point at which they can transition out of unemployment because they become eligible to receive pension benefits. We use a unique dataset covering the unemployment histories (longitudinal data) of individuals born between 1940 and 1965 who were registered with any of the public employment offices in Poland. Thus, we study a whole population of individuals who experienced this type of transition over the time period 1996-2015. We examine the transition from unemployment to retirement as a multi-year process. We analyse multiple unemployment spells, identify transition pathways, and look for patterns in these transitions. Moreover, we estimate a conditional risk set model (a stratified Cox model). Our research proves that being close to the point at which they are eligible to receive pension benefits leads individuals 'wait' to fulfil these eligibility criteria.
Keywords: C14; C41; H55; J14; J22; J26; J64; 330; elder workers unemployment; retirement; transition pathways; multiple unemployment spells; recurrent event data; longitudinal analysis